Gastric Biopsies: The Gap between Evidence-Based Medicine and Daily Practice in the Management of Gastric Helicobacter pylori Infection - Hala El-Zimaity; Stefano Serra; Eva Szentgyorgyi; Rajkumar Vajpeyi; Amir Samani (Canadian Journal of Gastroenterology)
BACKGROUND: Many consider histology to be the gold standard for Helicobacter pylori detection. Because the number and distribution of H pylori organisms vary, particularly in patients taking proton pump inhibitors (PPIs), the American Gastroenterological Association recommends discontinuing PPIs two weeks before endoscopy, and taking biopsies from both the body and antrum.